Tinjauan Perpajakan atas Transaksi Pemanfaatan Musik pada Lembaga Manajemen Kolektif - Fafa Zawawi; Budiasih Widiastuti (Jurnal Ekonomi Akuntansi dan Manajemen, 2021)
Music is a work of intellectual property and art that can become a national potential that must be protected. As technology develops, bush communities are close to music in their daily lives for entertainment, industry, commercial and education. And also makes music or songs more quickly known in the ears of listeners thereby increasing its utilization. The creator or owner of the right to use the music has the right attached to it to get compensation for the use of copyright and / or related rights or commonly known as royalties. The creator or right owner must be a member of the Collective Management Institute (LMK) to be able to obtain economic rights in the form of royalties so that only LMK, the representative of the creator or right owner, collect and distribute royalties. LMK as a non-profit entity receives income in the form of fees or commissions for the total income received from the beneficiaries. Of course, income from the use of music has been deducted by income tax article 23 and can be used as a tax credit with annual income tax payable. The question arises as to who exactly the income is attributed to and who is entitled to the tax credit, as well as how the taxation aspects of the distribution of royalties to the creator or right holder so that in an effort to support effective tax administration and on the basis of justice. Keywords: Royalty Income Tax, Collective Management Institute, Music Utilization